Educational Administration Innovation and Its Role in Effective Learning Environments - Dian Suherman (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2025)
Innovation in educational administration has become a critical driver for improving learning environment effectiveness in the context of digital and organizational transformation. This study examines how administrative innovation, supported by technology integration, transformational leadership, and data-driven management, contributes to the development of effective learning environments. Using a qualitative descriptive approach, data were collected through interviews, participant observation, and document analysis involving school leaders, teachers, and administrative staff. Thematic analysis was applied to identify key patterns related to administrative efficiency, instructional support, staff development, and student engagement. The findings indicate that the adoption of digital administrative systems, including learning and school management platforms, significantly reduces administrative workload, enhances operational efficiency, and strengthens evidence-based decision-making. Furthermore, the integration of technology-supported and project-based learning practices fosters higher levels of student engagement, motivation, and learning achievement. Continuous professional development and collaborative organizational culture emerge as essential enablers of sustainable innovation, supported by transformational leadership that promotes openness to change and shared responsibility. Despite challenges related to infrastructure constraints and resistance to change, systematic and well-coordinated innovation initiatives contribute positively to instructional quality, inclusivity, and overall school effectiveness. This study contributes to the educational administration literature by providing empirical insights into how innovation functions as an integrative process linking management practices, leadership, and learning outcomes. The findings offer practical implications for policymakers, school leaders, and educators seeking to design and implement sustainable administrative innovations that enhance learning environments in diverse educational contexts.